IMPROVING STUDENTS™ ACHIEVEMENT IN WRITING RECOUNT TEXT BY USING STUDENT TEAMS ACHIEVEMENT DIVISION METHOD - Mardhiah, Aini -; Ownie, Sri Juriaty (Universitas Negeri Medan, 2014)
Abstract This study aims to improve students™ achievement in writing recount text by using Student Teams Achievement Division (STAD) method. This Study was conducted by using classroom action research. The subject of the research was class X students of SMA Swasta Kebangsaan Denai Medan which consisted of 31 students. The research was conducted in two cycles and every cycle consisted of three meetings. The instrument of collecting data were quantitative (writing test) and qualitative data (diary notes, observation, and interview). Based on writing test scores, students™ score kept improving in every test. The mean score of the first cycle was was 68,3, in the second cycle, the mean score was 76. Based on the diary notes, observation, and interview, it was found that teaching-learning process ran well. Students were active, enthusiastic, and interested in writing. The result of the research showed that Student Teams Achievement Division (STAD) method could significantly improve students™ achievement in writing recount text. Keywords: STAD (Student Teams Achivement Division Method), Writing, Experimental Design, Recount Text